Pengaruh Good Corporate Governance, Reputasi Audit, Dan Leverage Terhadap Integritas Laporan Keuangan Dengan Moderasi Kualitas Audit - Novina, Helvira Aprilia; Muhsin; Juanda Astarani (Akmenika: Jurnal Akuntansi dan Manajemen, 2024)
This research is quantitative research which aims to analyze the influence of Good Corporate Governance, auditor reputation, and leverage on the integrity of financial reports with audit quality as a moderating variable. The research was conducted on mining sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The data used is secondary data with a purposive sampling method. The data testing techniques used include the classic assumption test, multiple linear regression test, and moderated regression analysis (MRA) test. The research results show that GCG and auditor reputation have no effect, while leverage has a positive effect on the integrity of financial reports. Meanwhile, audit quality is unable to moderate the influence of GCG, auditor reputation, and leverage on the integrity of financial reports. Therefore, companies need to pay attention to factors that can affect the integrity of financial reports, especially related to the company's debt level.